How is gender being addressed in the international development evaluation literature? A meta-evaluation. Issue 2 (23rd January 2019) - Lam, Steven; Dodd, Warren; Whynot, Jane; Skinner, Kelly
Abstract: Gender equity is an increasingly discussed priority and cross-cutting theme within international development evaluation. However, it is unclear whether advances being made in evaluating the outcomes in this area are reflected in the scholarly literature. In this context, a fundamental question is: How is gender being addressed in international development evaluation? To answer this question, we conducted a meta-evaluation to identify, synthesize, and assess published evaluation studies in international development with a focus on gender. We searched the Web of Science™ Core Collection database along with nine evaluation-focused journals using variations of the terms 'program evaluation' and 'gender'. A total of 2027 studies were identified, of which 70 met a priori inclusion criteria. Of the reviewed evaluations, many targeted gender-specific programs and specifically women. While the number of studies that report on gender is growing, and nearly all studies included gender-disaggregated data, often only outcomes by 'women' and 'men' were considered without going further to raise larger questions of gender equity. For evaluation to further contribute to gender equity, we suggest that future peer-reviewed evaluation studies provide data on diverse groups of genders, engage with evaluation stakeholders, consider the larger socio-cultural-political context of programming, encourage the use of evaluation findings, and provide actionable recommendations.